UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SOSIOLOGI MELALUI METODE RESITASI (RECITATION METHOD) PADA SISWA KELAS XI IPS.1 SMA N 1 TALAMAU - Azmalena, Azmalena (Jurnal Manajemen Pendidikan, 2017)
Based on student learning outcomes Class XI IPS.1 SMA N 1 Talamau in the subjects of Sociology found that student learning outcomes in the subjects Sociology is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about efforts Improving student learning outcomes in subjects Sociology sub Analyzing the diversity of social groups in multicultural society through Recitation Method (Recitation Method) in Class XI IPS.1 SMA N 1 Talamau Kabupaten Pasaman Barat. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 25 students of Class XI IPS.1 SMA N 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been raised, it can be concluded that Recitation Method (Recitation Method) can improve student learning outcomes in subjects Sociology sub Analyze the diversity of social groups in multicultural society SMA N 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 58.32 (Enough) increased to 83.76 (Good) with an increase of 25.44%